Creating an appropriate adaptation of a healthy lifestyle intervention for people after stroke. (18th September 2020) - Driver, Simon; McShan, Evan; Swank, Chad; Grobe, Katherine; Calhoun, Stephanie; Bailey, Ryan; Kramer, Kaye
ABSTRACT: Primary Objective: To describe (1) an evidence-based approach to promoting a healthy lifestyle, the Diabetes Prevention Program Group Lifestyle Balance intervention, and (2) our work with input from an Advisory Board of stakeholders to modify the program to meet the unique needs of people post stroke. Research Design: Community-Based Participatory Research Methods and Procedures: An Advisory Board of stakeholders was convened to modify the Group Lifestyle Balance intervention to meet the unique needs of people post stroke. Main Outcomes and Results: The primary adaptations that emerged from the Advisory Board included (1) curriculum emphasis on heart health after stroke, (2) care partner participation, (3) physical activity, dietary, and weight loss modifications specific to people after stroke, and (4) general programmatic recommendations (e.g., wider age range of participants; eligibility based on time since stroke; alternative modes of delivery). Conclusions: Feedback from the diverse group of stakeholders provides the basis for modifying an evidence-based healthy lifestyle intervention to meet the unique needs of people after stroke. Future research efforts should examine the efficacy and effectiveness of the adapted program to prevent weight gain after stroke and reduce the risk of chronic conditions including diabetes, metabolic syndrome, and heart disease.